2004
DOI: 10.1515/bmt.2004.024
|View full text |Cite
|
Sign up to set email alerts
|

Newly Explored Electrical Properties of Normal Skin and Special Skin Sites / Neue Untersuchungen zu elektrischen Eigenschaften normaler Haut und spezieller Hautpunkte

Abstract: Skin impedance measurements at various skin sites yield different impedance loci for normal skin and special skin sites. The results of skin impedance measurements taken at such sites with a two-electrode measurement system are presented herein. Some of these sites can be identified as acupuncture points. Data from 4 volunteers were acquired by means of a data acquisition board and a measuring system consisting of the measurement circuit, including several electrode types, and a power supply. The Cole model is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Scientific evidence suggested that ear skin impedance at the APs is electrically distinct from non-AP sites and that changes in ear skin AP impedance could be of substantial diagnostic, therapeutic, and research significance. Indeed, in China and certain western countries, different researchers have tried to demonstrate a difference between the skin impedance at AP and the surrounding impedance and showed that APs had lower skin resistance than nearby non-AP sites [ 20 , 21 ], which is useful in localization of APs. Moreover, another study showed that skin impedance at AP sites could be either lower or, in contrast to common belief, higher compared to the surrounding area and that this phenomenon had a high short-term and a low long-term reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence suggested that ear skin impedance at the APs is electrically distinct from non-AP sites and that changes in ear skin AP impedance could be of substantial diagnostic, therapeutic, and research significance. Indeed, in China and certain western countries, different researchers have tried to demonstrate a difference between the skin impedance at AP and the surrounding impedance and showed that APs had lower skin resistance than nearby non-AP sites [ 20 , 21 ], which is useful in localization of APs. Moreover, another study showed that skin impedance at AP sites could be either lower or, in contrast to common belief, higher compared to the surrounding area and that this phenomenon had a high short-term and a low long-term reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…그 예로 인체의 경혈이 낮은 피부저항 및 높은 전 기전도성을 갖는 특이점임을 밝히는 연구가 있었고 [5][6][7] , 침 자극이 신경전달과정이나 내분비 세포에 영향을 미친다는 연구 8,9) 가 있었으며, 자침에 따른 반응속도의 즉시성을 예 로 들어 침의 효과가 전기적인 에너지의 전달과 관련이 된 다는 연구 사례도 있었다 10,11) . 특히, 미약전자기적 측면에 서 혁신적인 측정 장비의 발달 [12][13][14] 과 궤를 같이하여 인체 의 경맥체계가 생체전자기적으로 특이적임을 밝히는 여러 연구가 있었다 [15][16][17] . 보다 구체적으로는 "고감도 자기장 측 정 장치인 superconducting quantum interference device(SQUID)를 이용하여 뇌, 심장 등에서 발생하는 생 체 자기장을 측정한 결과 자기장과 자침효과의 상관성이 다각도로 확인된다" 18) 거나 "경혈이 전자기 신호를 전달하 는 중요한 지점이라는 증거가 확인되었으며 침으로 경락을 따라 존재하는 경혈들을 자극하면 체내 전기신호가 평상시 보다 더 빨리 전달된다" 19) , "동일한 자극에 대한 경혈 및 비 경혈에 대한 전기적 특성이 차이가 있다" 20 21,22) .…”
Section: ⅰ 서 론unclassified
“…Most of devices are based on a two-electrode method, which may cause significant fluctuation of voltage between the two electrodes due to variable contact impedance between electrodes and tissue. Moreover, variation of pressure on electrodes, angle, or duration of the measurement also can influence the results [10, 12, 13, 16, 17]. However, a four-electrode method can minimize error due to electrode-sample contact resistance, which is serious in two-electrode method [15, 20].…”
Section: Introductionmentioning
confidence: 99%